Global trends and hotspots of exercise interventions for mild cognitive impairment: A global bibliometric analysis - Yi, Qing; Wang, Shuo; Feng, Xiaowei; Liu, Xutao; Selvanayagam, Victor Selvarajah; Cheong, Jadeera Phaik Geok (Lippincott Williams and Wilkins, 2024)
Background: Exercise interventions for mild cognitive impairment (MCI) have been extensively studied. However, there is no bibliometric study on exercise interventions for MCI. This study aimed to identify the collaborative networks, research hotspots, evolution trends, and future directions. Methods: Relevant documents were retrieved from the Web of Science Core Collection database. VOSviewer was used to analyze the co-authorship of the author, countries and institutions, and the keywords co-occurrence. CiteSpace was used to detect burst keywords' research trends. Results: A total of 569 articles were included and showed an overall increasing trend in annual publications. The most influential subject categories, authors, journals, country, and institutions were "geriatrics gerontology,""Doi, Takehiko and Shimada, Hiroyuki,""Journal of Alzheimer's Disease,"USA, and "Veterans Health Administration,"respectively. The research hotspots are "effectiveness,""neural mechanism"and "correlation"of exercise interventions, and the emerging trend is "intervention quality."Conclusion: This area is in a rapid development phase, whereby research hotpots are focused and the research trend is clear. The highly productive authors and institutions have made outstanding contributions and the subject categories present an interdisciplinary trend. However, there is weak cooperation between countries and institutions, and a substantial research gap exists between developed and developing countries. Future research may highlight the intervention quality, emphasizing the combination with virtual reality technology.